PD-1/PD-L1 Inhibitors in Patients With Preexisting Autoimmune Diseases - Zhang, Ke; Kong, Xiangyi; Li, Yuan; Wang, Zhongzhao; Zhang, Lin; Xuan, Lixue (Frontiers in Pharmacology, 2022)
Autoimmune diseases and malignant tumors are the two hotspots and difficulties that are currently being studied and concerned by the medical field. The use of PD-1/PD-L1 inhibitors improves the prognosis of advanced tumors, but excessive immune responses can also induce immune-related adverse events (irAE). Due to this concern, many clinical trials exclude cancer patients with preexisting autoimmune disease (AID). This review outlines the possible mechanisms of irAE, discusses the safety and efficacy of PD-1/PD-L1 inhibitors in cancer patients with preexisting AID, and emphasizes the importance of early recognition, continuous monitoring, and multidisciplinary cooperation in the prevention and management of cancer patients with preexisting AID.